PENGARUH BIAYA PRODUKSI TERHADAP LABA BERSIH DENGAN VOLUME PENJUALAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Lumbangaol, Romasi; Manik, Riri Swita (UNIKA Santo Thomas, 2024)
This study aims to analyze the effect of production costs on net profit and to examine that sales volume is a moderating variable in the relationship between production costs and net profit. The population of the study consists of textile and garment companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2020 period. The sample that met the criteria includes 11 companies over a 5-year observation period, resulting in a total of 55 analysis units. The data analysis techniques used are simple regression analysis and moderated regression analysis (MRA) with an interaction approach, utilizing SPSS version 25 The hypothesis testing results indicate that production costs have a positive and significant effect on the company's profit. Additionally, the interaction test or MRA shows that sales volume, as a moderating variable, can strengthen the moderation of production costs on net profit.